2011
DOI: 10.1097/qai.0b013e318202bf7d
|View full text |Cite
|
Sign up to set email alerts
|

HIV Partner Notification Is Effective and Feasible in Sub-Saharan Africa: Opportunities for HIV Treatment and Prevention

Abstract: Background Sexual partners of persons with newly diagnosed HIV infection require HIV counseling, testing and, if necessary, evaluation for therapy. However, many African countries do not have a standardized protocol for partner notification and the effectiveness of partner notification has not been evaluated in developing countries. Methods Individuals with newly diagnosed HIV infection presenting to STI clinics in Lilongwe, Malawi were randomized to one of three methods of partner notification: passive refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
237
7
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(267 citation statements)
references
References 26 publications
21
237
7
2
Order By: Relevance
“…An important fact in this study was that all partner notifications were made by the index patients themselves, which may be associated with the type of relationship they have, as this is the most viable notification method for stable relationships (with affectional bond regardless of a marital relationship) when compared to casual sex (outside the context of a relationship) (13,18) . On the other hand, it may be a concern if the sexual behavior with high potential for STI transmission, in particular HIV, is focused on casual sex (4) . However, the lack of studies addressing this theme in Brazil does not allow to have a better understanding of how partners are being notified by health services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important fact in this study was that all partner notifications were made by the index patients themselves, which may be associated with the type of relationship they have, as this is the most viable notification method for stable relationships (with affectional bond regardless of a marital relationship) when compared to casual sex (outside the context of a relationship) (13,18) . On the other hand, it may be a concern if the sexual behavior with high potential for STI transmission, in particular HIV, is focused on casual sex (4) . However, the lack of studies addressing this theme in Brazil does not allow to have a better understanding of how partners are being notified by health services.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the national recommendation methods, there is no study in the country showing how partners are notified and what strategies are currently used in health services. Improper notification is one of the main factors associated with the challenge of STI control (4)(5) , especially syphilis, whose non-treatment of partners of infected pregnant women is frequently mentioned as one of the causes of congenital syphilis in the country (6) . In the United States and in Europe, partner notification has become a strategy of HIV prevention, and it is related to the increased search for counseling and testing among sexual partners notified by index patients diagnosed with the virus (1)(2)4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, two recently reported trials, one each from Cameroon and Malawi, 2,3 suggestions for obtaining evidence on multiple fronts to solve this puzzle. Here is not the place to summarize this exceptional analysis of the realities on the ground, only to point out a relevant omission: nowhere in their report do the authors suggest using PN/contact tracing as a potentially useful investigatory tool to help close this "research gap" 7 and neither do the seasoned researchers.…”
Section: Pilot Testing Hiv Pn and Its Uses In Sub-saharan Africamentioning
confidence: 99%
“…Both historically and presently, most investigations into the HIV epidemics in sub-Saharan Africa have (surprisingly) focused almost exclusively on sexual intercourse variables and related risk markers. 9 Rarely are non-sexual modes of transmission considered or measured, a criticism that extends to the otherwise well-conducted PN trials in Cameroon and Malawi, 2,3 where named sexual partners who were identified as HIVinfected were presumed to have acquired HIV, by default, from sex. No attempt was apparently made to consider or investigate non-sexual exposures.…”
Section: Pilot Testing Hiv Pn and Its Uses In Sub-saharan Africamentioning
confidence: 99%